Development and sexual dimorphism of the sonic system in three deep-sea neobythitine fishes and comparisons between upper mid and lower continental slope. (January 2018) - Fine, Michael L.; Ali, Heba A.; Nguyen, Thanh Kim; Mok, Hin-Kiu; Parmentier, Eric
Abstract: Based on morphology, NB Marshall identified cusk-eels (family Ophidiidae) as one of the chief sound-producing groups on the continental slope. Due to food scarcity, we hypothesized that sonic systems will be reduced at great depths despite their potential importance in sexual reproduction. We examined this hypothesis in the cusk-eel subfamily Neobythitinae by comparing sonic morphology in Atlantic species from the upper-mid ( Dicrolene intronigra ) and deeper continental slope ( Porogadus miles and Bathyonus pectoralis ) with three Taiwanese species previously described from the upper slope ( Hoplobrotula armatus, Neobythites longipes and N. unimaculatus ). In all six species, medial muscles are heavier in males than in females. Dicrolene has four pairs of sonic muscles similar to the shallow Pacific species, suggesting neobythitine sonic anatomy is conservative and sufficient food exists to maintain a well-developed system at depths exceeding 1 km. The sonic system in Porogadus and Bathyonus was reduced to a single pair of ventral medial muscles that connects to a smaller and thinner swimbladder via a long tendon. Small muscle fiber diameters, a likely indicator of rapid contraction, were present in males of five of the species. However, in Bathyonus, the deepest species (pale coloration, reduced eye size, shorter sonic muscles and longer tendons), muscle fibers were larger suggesting an adaptation to facilitate rapid bladder movement for sound production while using slower contractions and less metabolic energy. The six species separate into three groups in length-weight regressions: the three upper slope species have the greatest weights per unit length, Dicrolene is lower, and the two deep species are further reduced consistent with the hypothesis that food limitation affects sonic anatomy at great depths. Highlights: Deeper neobythitines have longer tails and lower body weights per unit length. Medial swimbladder muscles are larger in males suggesting sexual selection for enhanced sound production. Sonic systems are conservative in shallow neobythitines. Deeper species have reduced the number of sonic muscles and have extremely long tendons. Sonic systems, suggesting sound production, occur in cusk-eels from shallow water to 5 km.